Boreogadus saida - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Boreogadus saida (Lepechin, 1774). Arctic Cod or Polar Cod. To 46 cm (18.1 in) TL (Wienerroither et al. 2011), usually less than 25 cm (9.8 in) (Cohen in Cohen et al. 1990). The largest we know of from our area is a specimen from the Chukchi Sea measuring 30 cm (12 in) TL (Alverson and Wilimovsky 1966). Circumpolar in Arctic (Cohen in Cohen et al. 1990); Arctic Siberia to Cape Olyutorskiy, western Bering Sea; Beaufort Sea (Frost and Lowry 1981) to Bristol Bay, south-eastern Bering Sea (Allen and Smith 1988). Taken as far north as 88°26’N, 126°26’E (Mecklenburg et al. 2007). Brackish lagoons, river mouths (Morrow 1980), and ocean; depth: surface to at least 1,390 m (4,559 ft) (min.: Renaud in Coad and Reist 2018; max.: Mecklenburg et al. 2011). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 80, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008